Peningkatan Kinerja Guru Tersertifikasi Menggunakan Metode Pekak dan Evaluasi Kinerja di Dabin I UPT TK/SD Kecamatan Kedungtuban - Suswatiningsih, Sri Rahayu (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The purpose of this research is to improve the certificated teachers’ performance through Pekak Method and performance evaluation on Region I Preschool/Elementary School Division Sub-District ofKedungtuban. This research is an action research with 38 subjects. This research takes on Second Semester of 2016/2017 Year Academic.The tools of collecting data are interview guidance, sheet of observation and sheet of performance evaluation. This research is consist of two cycles. The result of this research is the improvement of the certificated teachers’ performance from low level becomes high level. On the Early Condition, the certificated teachers’ performance is on the low level with average as 61 and completeness as 11,8%. On the First Cycle, the certificated teachers’ performance is on the middle level with average as 73 and completeness as 47,5%.On the Second Cycle, the certificated teachers’ performance is on the high level with average as 80 and completeness as 94,9%.